2015
DOI: 10.1111/ocr.12100
|View full text |Cite
|
Sign up to set email alerts
|

The effect of antimicrobial agents on bond strength of orthodontic adhesives: a meta‐analysis of in vitro studies

Abstract: Antimicrobial orthodontic adhesives aim to reduce white spot lesions' incidence in orthodontic patients, but they should not jeopardizing its properties. Systematic review and meta-analysis were performed to answer the question whether the association of antimicrobial agents with orthodontic adhesives compromises its mechanical properties and whether there is a superior antimicrobial agent. PubMed and Scopus databases. In vitro studies comparing shear bond strength of conventional photo-activated orthodontic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 47 publications
(78 reference statements)
1
12
0
Order By: Relevance
“…adhesive mode compared to other groups in this study (Figure 2). However, our results are in accordance with the results of a recent meta-analysis [25], where it is affirmed that the incorporation of antimicrobial agents into an orthodontic adhesive does not influence bond strength to enamel. It was also demonstrated that higher SBS may lead to sound enamel loss during bracket debonding [26].…”
Section: Discussionsupporting
confidence: 92%
“…adhesive mode compared to other groups in this study (Figure 2). However, our results are in accordance with the results of a recent meta-analysis [25], where it is affirmed that the incorporation of antimicrobial agents into an orthodontic adhesive does not influence bond strength to enamel. It was also demonstrated that higher SBS may lead to sound enamel loss during bracket debonding [26].…”
Section: Discussionsupporting
confidence: 92%
“…Recently, a systematic review 5 demonstrated that the incorporation of antibacterial agents into orthodontic adhesives showed no difference in shear bond strength. One related study 6 performed antibacterial growth assay in liquid media with 250 and 500 ppm of silver nanoparticles against S. mutans without compromising shear bond strength; however, no significant antibacterial growth was found after 24 h. Instead, in our study the inhibitory growth effect of silver nanoparticles was achieved with amounts of 500, 800, and 1500 ppm.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, bond strength is higher in increased solvent-free adhesive systems, while the rate of leakage is likely to decrease with the use of additional layers (8). Another research in this regard suggested the use of two layers of self-etching primers to facilitate the bonding process (17); as such, the bond strength could improve with increased number of overlying layers in two all-in-one adhesive systems. According to the results of the current study, storage of samples in artificial saliva for three months without the use of margin bond reduced the SBS rate in all adhesive systems, while it significantly increased the SBS rate of the SBMP adhesive, and this increase was not considered significant in the SBS rate of the Clearfil SE bond.…”
Section: Discussionmentioning
confidence: 99%